2020
DOI: 10.1037/men0000253
|View full text |Cite
|
Sign up to set email alerts
|

“We don’t talk about feelings or struggles like that”: White men’s experiences of eating disorders in the workplace.

Abstract: Masculine qualities are highly prized in the workplace, and men who deviate from these standards may experience personal and organizational backlash for their inability or unwillingness to perform masculinity. Additionally, those with mental health problems face complications managing their conditions at work due to organizational and interpersonal challenges. In the current study, we examine the intersection of masculinity and mental health in the workplace, focusing specifically on White men with eating diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…Six studies reported how mental illness stigma and men's fear of transgressing masculine cultures normed by strength, independence, and invincibility, can play out in male-dominated environments such as places of paid work and professional sport (DeLenardo & Terrion, 2014;Hassouneh & Fornero, 2020;Mahalik & Dagirmanjian, 2019;Siegel & Sawyer, 2019;Staiger et al, 2020;Wood et al, 2017). Consistently reported by men in these studies was the fear of being perceived as weak, incapable of coping with distress, and failing to fulfill the masculine norms deemed mandatory for specific male dominated jobs and sports.…”
Section: Stigma In Male-dominated Environmentsmentioning
confidence: 92%
“…Six studies reported how mental illness stigma and men's fear of transgressing masculine cultures normed by strength, independence, and invincibility, can play out in male-dominated environments such as places of paid work and professional sport (DeLenardo & Terrion, 2014;Hassouneh & Fornero, 2020;Mahalik & Dagirmanjian, 2019;Siegel & Sawyer, 2019;Staiger et al, 2020;Wood et al, 2017). Consistently reported by men in these studies was the fear of being perceived as weak, incapable of coping with distress, and failing to fulfill the masculine norms deemed mandatory for specific male dominated jobs and sports.…”
Section: Stigma In Male-dominated Environmentsmentioning
confidence: 92%
“…The review identified 26 studies, including 16 qualitative [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], 7 quantitative [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and 3 mixed-methods studies [ 52 , 53 , 54 ]. Table 1 summarizes the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…We had trouble recruiting cis-men; only 8% of those men approached participated, compared to 33% of women, 50% of trans men, and 100% of nonbinary people. Difficulty recruiting men to participate in research that asks them to discuss a personal experience or a sensitive topic is not unique (Butera, 2006;Siegel & Sawyer, 2020). Butera (2006) states that men's refusal to participate is one way that they perform masculinity and that men are more likely to participate when they feel certain that the research with allow them to perform their masculinity well (p. 1274).…”
Section: Methodsmentioning
confidence: 99%